Local Contingencies in L2 Tasks: A Comparison of Context-Sensitive Interactional Achievements across Two Different Task Types - Ufuk Balaman (Universitat Autònoma de Barcelona, 2017)
Recent research on L2 interaction and interactional competencies shows that L2 learners deploy a great diversity of interactional resources and adapt their talk to context-sensitive differences in various institutional settings. Although there is a growing interest in how these resources vary in different settings, comparative investigations into the interactional mechanisms in different contexts is scarce. With this mind, using Conversation Analysis, this study sets out to provide a snapshot of how a focal L2 learner manifests an observable diversity in task openings of a face-to-face discussion task and an online emergent information gap task. We focus on the first encounters with these two task types and settings and describe participant orientations to context-sensitive conduct on a turn-by-turn basis. The findings demonstrate differences in turn taking, allocation and design as well as in action formation, thus contributing to L2 interactional competence research based on comparative analyses of two single cases.